2023
DOI: 10.3389/fpubh.2023.1268470
|View full text |Cite
|
Sign up to set email alerts
|

Medical insurance, health risks, and household financial asset allocation: evidence from China household finance survey

Chengming Li,
Jiashan Li,
Chenchen Zhai
et al.

Abstract: There is a lack of micro evidence on whether medical insurance may optimize the household financial asset allocation by transferring health risk, despite the fact that health risk is a significant component driving families’ precautionary savings. This article empirically examines the impact of health risk and social medical insurance on household risky financial asset allocation using a Probit model, based on data from the 2015–2019 China Household Finance Survey (CHFS). The findings indicate that social medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
0
0
Order By: Relevance
“…Digital finance in general has a ‘digital dividend’ effect ( 18 , 19 ), reducing income disparities and bridging the ‘digital divide’ ( 20 ). For individuals, the increase in earning capacity and income levels, the increased awareness of self-protection and the costs of risk protection ( 21 ), the change in risk preferences and the fear of returning to poverty ( 22 , 23 ), and the pursuit of individual and structural optimisation within the framework of rational choice ( 1 ) will facilitate participation in or supplementation with health insurance ( 24 ). In addition, Wang et al ( 25 ) found a mediating effect mechanism for the income effect in the study exploring the impact of digital finance on social security from a macro perspective.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Digital finance in general has a ‘digital dividend’ effect ( 18 , 19 ), reducing income disparities and bridging the ‘digital divide’ ( 20 ). For individuals, the increase in earning capacity and income levels, the increased awareness of self-protection and the costs of risk protection ( 21 ), the change in risk preferences and the fear of returning to poverty ( 22 , 23 ), and the pursuit of individual and structural optimisation within the framework of rational choice ( 1 ) will facilitate participation in or supplementation with health insurance ( 24 ). In addition, Wang et al ( 25 ) found a mediating effect mechanism for the income effect in the study exploring the impact of digital finance on social security from a macro perspective.…”
Section: Theoretical Backgroundmentioning
confidence: 99%